Implementation of The Talent Management Program at PT Savoria Kreasi Rasa Area Head Office Jakarta Pusat - Andrian, Diky; Handayani, Dyah Octavia; Digdowiseiso , Kumba (CV ODIS, 2024)
Talent management is critical in developing human resources in every company. Talent management is about having a competent and experienced team and a process that includes various stages, including employee resource search, recruitment, and continuous development to encourage employee retention. To measure policy effectiveness, PT. Savoria Kreasi Rasa Area Head Office Central Jakarta uses General Electric theory, emphasizing four main aspects: Attract, Develop, Manage, and Retain. This research uses qualitative analysis methods to provide valuable insights for company management, human resource practitioners, talent management, and organizational development researchers. The results of this research show several factors that influence talent management, starting from the business achievements first, succession planning, a recruitment process by the required criteria based on MPP (Man Power Planning), carrying out the onboarding process for new employees, an assessment system employees use Key Performance Appraisal (KPA), develop training, and communicate through the Savoria Portal. Talent management at PT. Savoria Kreasi Rasa Area Head Office Central Jakarta has been running quite well. However, its implementation has several shortcomings, so it is still in development, with room for improvement